Pengaruh Penguasaan Bahasa Indonesia terhadap Pemahaman Teori dan Praktik Pendidikan Jasmani pada Mahasiswa - Ika Febriana; Muhammad Reza Nasution; Bayu Christo Anugrah Purba; Della Wiyanti; Nurul Ikhwani (Universitas Palan, 2024)
The mental and physical health of students is greatly influenced by physical education, especially in the Physical Education, Health, and Recreation (PJKR) study program at Medan State University. One of the languages ​​that can be used in PJKR learning to understand the Theory and Practice of Education and to communicate with lecturers and friends during lectures is Indonesian. The purpose of this study was to determine the effect of Indonesian language proficiency on students' understanding of physical education theory and practice. This is because language is an important communication tool in learning, including in physical education lessons. The results of the study showed that increasing Indonesian language proficiency has an effect on contributing to improving student achievement in the field of Physics education.